Histories of the aftermath : the legacies of the Second World War in Europe ; [ ... contributions to a conference, that was held at the University of California, San Diego] - Biess, Frank 1966- Hrsg; Moeller, Robert G. 1949- (Berghahn Books, 2010)
Introduction / Frank Biess -- Defining the postwar -- The persistence of "the postwar" : Germany and Poland / Norman M. Naimark -- Feelings in the aftermath : toward a history of postwar emotions / Frank Biess -- In the aftermath of camps / Samuel Moyn -- Public and private memories -- Nothing is forgotten : individual memory and the myth of the Great Patriotic War / Lisa A. Kirschenbaum -- Neither erased nor remembered : Soviet "women combatants" and cultural strategies of forgetting in Soviet Russia, 1940s-1980s / Anna Krylova -- Generations as narrative communities : on the private sources of official cultures of remembrance in postwar Germany / Dorothee Wierling -- Mass-mediating war : how movies shaped memories -- "When will the real day come?" War films and Soviet postwar culture -- Denise Youngblood -- "Winning the peace" at the movies : suffering, loss, and redemption in postwar German cinema / Robert G. Moeller -- Italian cinema and the transition from dictatorship to democracy / Ruth Ben-Ghiat -- The reconstruction of citizenship -- War orphans and postfascist families : kinship and belonging after 1945 / Heide Fehrenbach -- Manners, morality, and civilization : reflections on postwar German etiquette books / Paul Betts -- From the "New Jerusalem" to the "decline" of the "New Elizabethan Age" : national identity and citizenship in Britain, 1945-56 / Sonya O. Rose -- "We are building a common home" : the moral economy of citizenship in postwar Poland / Katherine Lebow -- In the shadow of the bomb : military cultures -- The great tradition and the fates of annihilation : West German military culture in the aftermath of the Second World War / Klaus Naumann -- Soviet military culture and the legacy of the Second World War / Mikhail Tsypkin -- 1945-1955 : the age of total war / Pieter Lagrou